2015
DOI: 10.1002/anie.201500233
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalyzed CO2 Trapping Using Alkynyl Indoles

Abstract: The first organocatalyzed trapping of CO2 through C-C and C-O bond formation is reported. Alkynyl indoles together with catalytic amounts of an organic base and five equivalents of CO2 resulted in the formation new heterocyclic structures. These tricyclic indole-containing products were successfully prepared under mild reaction conditions from aromatic, heteroaromatic, and aliphatic alkynyl indoles with complete regioselectivity. Further investigations suggest that C-C bond formation is the initial intermolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 67 publications
4
49
0
Order By: Relevance
“…For computational efficiency, substrate 1 a (Scheme ) was used to investigate the three possible activation modes in Scheme . It is noteworthy that Skrydstrup and co‐workers reported the use of 3 equivalents of TBD to generate significant levels of 1 a at a lower temperature (70 °C) than the optimal temperature (100 °C) . This change was made to avoid the decomposition of 1 a at 100 °C.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…For computational efficiency, substrate 1 a (Scheme ) was used to investigate the three possible activation modes in Scheme . It is noteworthy that Skrydstrup and co‐workers reported the use of 3 equivalents of TBD to generate significant levels of 1 a at a lower temperature (70 °C) than the optimal temperature (100 °C) . This change was made to avoid the decomposition of 1 a at 100 °C.…”
Section: Resultssupporting
confidence: 74%
“…Based on the correlation between the catalytic activity and basicity properties of amines/guanidines in the reactions of CO 2 with propargylamines, the authors concluded that the basicity of the catalyst, rather than the formation of the CO 2 adduct, was responsible for the catalytic activity. This interesting finding raised obvious questions pertaining to the source of the catalytic activity in the CO 2 coupling reaction reported by Skrydstrup's group …”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…A TBD base was used by Skyrdrup to catalyze a carboxylation/cyclization reaction applied to 2-alkynyl indoles (127) with aromatic or aliphatic substituents at the alkyne unit (Scheme 53) to produce selectively the new heterocyclic structures 128 [128]. Aromatic 2-alkynyl indoles (R 2 = aryl, Scheme 53) (0.20 mmol) were reacted in the presence of 0.3 eq.…”
Section: Base-catalyzed Carboxylation Of 2-alkynyl Indoles With Co2mentioning
confidence: 99%